Association Between White Blood Cell Counts and Brachial-Ankle Pulse Wave Velocity in Chinese Hypertensive Adults: A Cross-Sectional Study. (January 2022) - Jia, Buyun; Jiang, Chongfei; Song, Yun; Duan, Chenfangyuan; Liu, Lishun; Liu, Chengzhang; Xu, Xiping; Qin, Xianhui; Chen, Guangliang
Increased arterial stiffness is highly prevalent in patients with hypertension and is associated with cardiovascular (CV) risk. Increased white blood cell (WBC) counts may also be an independent risk factor for arterial stiffness and CV events. The aim of the study was to investigate the relationship between differential WBC counts and brachial-ankle pulse wave velocity (baPWV) in hypertensive adults. A total of 14 390 participants were included in the final analysis. A multivariate linear regression model was applied for the correlation analysis of WBC count and baPWV. Higher WBC counts were associated with a greater baPWV: adjusted β = 10 (95% CI, 8-13, P < .001). The same significant association was also found when WBC count was assessed as categories or quartiles. In addition, the effect of differential WBC subtypes, including neutrophil count and lymphocyte count on baPWV, showed the similar results. These findings showed that baPWV has positive associations with differential WBC counts in hypertensive adults.